Kerklike eenheid tussen die Nederduitsch Hervormde Kerk van Afrika en die Hervormde Kerk in Suidelike Afrika 1 - Wyk, I. W. C. van (Hervormde teologiese studies, 2000)
Church unity between the Nederduitsch Hervormde Kerk van Afrika and the Hervormde Kerk in Suidelike Afrika. Church unity between the Nederduitsch Hervormde Kerk van Afrika (NHKA) and the Hervormde Kerk in Suidelike Afrika (HKSA) was a (heme that was not even discussed in the past. The reason: the mission policy of the NHKA was that the HKSA should become an independent and separate church as quickly as possible. During the last years many things changed. Article III in the Polity of the NHKA was scrapped. The NHKA is now an open church. The ideology of apartheid, that the NHKA supported in many ways, has crumbled. The time has therefore arrived to start discussing the important theological theme of church unity between these two churches. In this article the view is represented that church unity is not primarily unity in organisation, but unity in faith, confession, teaching and theology. This unity in faith, however, must be made visible. Various forms of ecumenical unity are therefore proposed.